Research priorities for freshwater mussel conservation assessment - Ferreira-Rodríguez, Noé; Akiyama, Yoshihiro B.; Aksenova, Olga V.; Araujo, Rafael; Barnhart, Miles Christopher; Bespalaya, Yulia V.; Bogan, Arthur E.; Bolotov, Ivan; Budha, Prem Bahadur; Clavijo, Cristhian; Clearwater, Susan J.; Darrigran, Gustavo Alberto; et al. (Biological Conservation)
Freshwater mussels are declining globally, and effective conservation requires prioritizing research and actions to identify and mitigate threats impacting mussel species. Conservation priorities vary widely, ranging from preventing imminent extinction to maintaining abundant populations. Here, we develop a portfolio of priority research topics for freshwater mussel conservation assessment. To address these topics, we group research priorities into two categories: intrinsic or extrinsic factors. Intrinsic factors are indicators of organismal or population status, while extrinsic factors encompass environmental variables and threats. An understanding of intrinsic factors is useful in monitoring, and of extrinsic factors are important to understand ongoing and potential impacts on conservation status. This dual approach can guide conservation status assessments prior to the establishment of priority species and implementation of conservation management actions. Fil: Ferreira-Rodríguez, Noé. Universidad de Vigo. Facultad de Ciencias; España Fil: Akiyama, Yoshihiro B. National Institute for Land and Infrastructure Management; Japón Fil: Aksenova, Olga V. Russian Academy of Sciences; Rusia Fil: Araujo, Rafael. Consejo Superior de Investigaciones Científicas. Museo Nacional de Ciencias Naturales; España Fil: Barnhart, Miles Christopher. University of Missouri; Estados Unidos Fil: Bespalaya, Yulia V. Russian Academy of Sciences; Rusia Fil: Bogan, Arthur E. North Carolina Museum of Natural Sciences; Estados Unidos Fil: Bolotov, Ivan. Northern Arctic Federal University; Rusia Fil: Budha, Prem Bahadur. Tribhuvan University; Nepal Fil: Clavijo, Cristhian. Ministerio de Educación y Cultura. Museo Nacional de Historia Natural; Uruguay Fil: Clearwater, Susan J. National Institute of Water and Atmospheric Research; Australia Fil: Darrigran, Gustavo Alberto. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Invertebrados; Argentina. Consejo Nacional de ...